Transient receptor potential a1b regulates primordial germ cell numbers and sex differentiation in developing zebrafish - Xiaoting Gong; Qianqian Yan; Liangbiao Chen (Journal of Fish Biology, 2025)
Temperature is a leading environmental factor determining the sex ratio of some animal populations, such as fish, amphibians, and reptiles. However, the underlying mechanism by which temperature affects gender is still poorly understood. Transient receptor potential a1b (Trpa1b) belongs to the ion channel family of transient receptor potentials and exhibits dual thermosensitivity to heat and cold. In this study, we have unveiled a novel function of the trpa1b gene. Zebrafish generated through clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 with Trpa1b‐null manifest a male‐biased sex ratio. The quantity of primordial germ cells (PGCs) in zebrafish is closely linked to gender determination and gonadal development. Yet the role of the trpa1b gene in zebrafish reproductive development remains unexplored in the literature. Our investigation revealed a significant reduction in PGCs in Trpa1b mutant zebrafish compared to their wild‐type counterparts 24‐h postfertilization (hpf). Transcriptome sequencing of tissues near the reproductive crest of embryos at 1.25 days postfertilization (dpf) revealed differential changes in PGC‐related marker genes and genes related to sperm cell development and differentiation. The relative expression of ddx4 and sycp3 genes was significantly downregulated, whereas amh was significantly upregulated at 20 dpf in trpa1b −/− zebrafish. The results of this study provide valuable insights and references for studying the molecular mechanism of sex determination in zebrafish. Undoubtedly, these results will further enhance our understanding of gender differentiation and gonadal development in fish and other vertebrates.